(untitled) (The Research of Medical Science Review, 2025)
Objective: To evaluate the surgical results associated with modified radical mastectomy using LigaSure diathermy and conventional scalpel dissection, focusing on operative time, estimated blood loss, occurrence of seromas, and postoperative complications. Place and Duration of Study: Department of General Surgery, Federal Government Polyclinic Hospital Islamabad. Study Design: Quasi Experimental Study Methodology: In the study, one hundred females who were undergoing modified radical mastectomy were divided into two equal groups of 50 each, with one receiving LigaSure and the other receiving the standard scalpel treatment. The patients’ demographic details were collected along with intraoperative blood loss, length of time spent in the operating theatre, formation of seroma, amount of drainage from the wound, postoperative complications, and histopathological examination. The independent t-test was used to check the means of continuous variables while the Chi-square test was used for categorical variables, with a 95% confidence interval. Results: LigaSure marked a notable difference in operative time which was significantly less compared to the control group (p=0.03). Loss of blood during the surgery was also on the lower side for LigaSure (p=0.02). Seroma formation was higher in the LigaSure group’s rate of 46%, compared to the scalpel group’s 30% (p=0.04). Drain output and duration were also significantly greater in the LigaSure group (p=0.03, p=0.02). There was no significant difference in the parameters of wound infection (p=0.07), hematoma formation (p=0.08), skin flap necrosis (p=0.12). Postoperative pain scores were lower in the LigaSure group (p=0.01). Conclusion: LigaSure significantly reduces operative time and blood loss but is associated with increased seroma formation and longer drain duration. It offers advantages in postoperative pain control but does not significantly impact wound infection or hematoma rates.